A New Explanation of Christological Origins: A Review of the Work of Larry W. Hurtado - Fletcher-Louis, Crispin H. T. (Tyndale bulletin, 2009)
Prof. Larry Hurtado’s three-volume work on christological origins has advanced understanding in several key respects and his account is simpler than that of his predecessors. However, it remains an evolutionary, multi-stage model and it is historically problematic. He overstates the case for Jewish opposition to Christ-devotion, minimises the ethical particularity of earliest Christianity and the model suffers some serious internal tensions. His claim that religious experiences gave the decisive impetus to Christ-devotion does not reckon adequately with the implications of social-science study, is not supported by the primary texts and conflicts with the important evidence that visionary and mystical practices were frowned upon in some early Christian quarters. Hurtado presents his work as theologically disinterested. However, he endorses Lessing’s radical separation of theology and history and this theologically loaded judgement seems to be reflected in the non-incarnational character of the Christology Hurtado describes.